Perubahan Fonologis dalam Kasus Arabisasi Lafaz-lafaz Persia pada Syair “Alamma Khayalun min Qutaylah” Karya Al-A’sya / Phonological Change in the Case of Arabization of Persian Words in the Poem “Alamma Khayalun min Qutaylah” by Al-A'sha - Azhar Ilham Haliwungan; Mathias Revando (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2024)
The Arabization of Persian phrases is found in Al-A'sha's poem entitled “Alamma Khayalun min Qutaylah”. This is because Al-A'sha was a delegate who had a strong relationship with Persian kings. This study aims to analyze the phonological changes in the case of the arabization of Persian words in the poem. This type of research is qualitative research, while the data sources are the book of Diwan Al-A'sha Al-Kabir and the Arabic-Persian dictionary as data sources. Data collection is done by library research technique. The literature review was conducted by looking for changes in the words in several dictionaries. With such data collection, it can be found the original Persian word before the arabization process occurred. In this study, the phonological approach is applied in content analysis by categorizing the phonological changes into several parts. The analysis of phonological changes is carried out using the school of ancient linguists, especially the school of Sibawaih. Based on the analysis, it can be found that there are four phonological changes, namely the replacement of consonants with consonants as in the word مِسك which is the result of the arabization of the Persian word مُشك, the replacement of vowels with vowels as in the word سَوسن which is the result of the arabization of the Persian word سُوسن, the addition of letters or the like as in the word جُلَّسان which is the result of the arabization of the Persian word جُلْشن, and the removal of letters as in the word مرزجوش which is the result of the arabization of the Persian word مرزنكوش.Abstrak: Arabisasi lafaz-lafaz Persia banyak ditemukan pada syair Al-A’sya yang berjudul “Alamma Khayalun min Qutaylah”. Hal ini karena Al-A’sya merupakan delegasi yang memilki hubungan kuat dengan raja-raja Persia. Penelitian ini bertujuan untuk menganalisis perubahan fonologis dalam kasus arabisasi lafaz-lafaz Persia pada syair tersebut. Jenis Penelitian ini adalah penelitian kualitatif, adapun sumber datanya adalah kitab Diwan Al-A’sya Al-Kabir dan kamus Arab-Persia sebagai sumber data. Pengumpulan data dilakukan dengan teknik kajian pustaka. Tinjauan pustaka dilakukan dengan mencari perubahan lafaz-lafaz tersebut dalam beberapa kamus. Dengan pengumpulan data yang demikian, dapat ditemukan lafaz Persia asli sebelum proses arabisasi terjadi. Dalam penelitian ini pendekatan fonologi diterapkan dalam analisis isi dengan mengkategorikan perubahan-perubahan fonologis menjadi beberapa bagian. Analisis perubahan fonologis dilakukan dengan menggunakan mazhab ahli bahasa zaman dulu khususnya mazhab Sibawaih. Berdasarkan analisis tersebut dapat ditemukan bahwa ada empat perubahan fonologis, yaitu penggantian konsonan dengan konsonan seperti pada kata مِسك yang merupakan hasil arabisasi kata Persia مُشك, penggantian vokal dengan vokal seperti pada kata سَوسن yang merupakan hasil arabisasi kata persia سُوسن, penambahan huruf atau sejenisnya seperti pada kata جُلَّسان yang merupakan hasil arabisasi kata Persia جُلْشن, dan penghilangan huruf seperti pada kata مرزجوش yang merupakan hasil arabisasi kata Persia مرزنكوش.